2016
DOI: 10.1097/ccm.0000000000001464
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Index Hospitalization and Hospital Readmission in Sepsis Survivors*

Abstract: We confirmed that the majority of unplanned hospital readmissions after sepsis are due to an infection. We found that patients with sepsis at admission who developed a hospital-acquired infection, and those who received a longer duration of antibiotics, appear to be high-risk groups for unplanned, all-cause 30-day readmissions and infection-related 30-day readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 30 publications
5
76
1
2
Order By: Relevance
“…The relationship between index sepsis hospitalization and unplanned hospital readmissions was demonstrated by Sun et al [24] in a retrospective cohort study in the USA. The study demonstrated that unplanned hospital readmissions after an episode of sepsis are common, and that infection was the commonest reason for readmission.…”
Section: Hospital Readmissionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between index sepsis hospitalization and unplanned hospital readmissions was demonstrated by Sun et al [24] in a retrospective cohort study in the USA. The study demonstrated that unplanned hospital readmissions after an episode of sepsis are common, and that infection was the commonest reason for readmission.…”
Section: Hospital Readmissionsmentioning
confidence: 99%
“…These studies [10,24] reinforce that more research is necessary to (1) understand better the risk factors associated with readmission after sepsis, (2) identify strategies to decrease the risk of readmission after sepsis, initially with observational cohort studies with propensity matching of readmitted and nonreadmitted patients, and then (3) prospective RCTs of interventions to ultimately define cost-effective interventions in sepsis survivors that decrease readmission rates after hospital discharge.…”
Section: Hospital Readmissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospital readmission is particularly common, with rates of 90-day readmission ranging from 30% to >40%(46). High readmission rates after sepsis have been seen in a variety of settings, suggesting that the problem is not unique to any particular healthcare system(3,5,7)…”
Section: Introductionmentioning
confidence: 99%
“…Second, although the study used several well-validated tools to assess the many domains that are impaired in ICU survivors, in the absence of consensus on the best tools to use in post-ICU outcomes research, comparison across studies is inherently challenging (15). Additionally, the study was not designed to investigate whether the intervention had any effect on hospital readmissions, a challenge faced by nearly one out of four sepsis survivors (16). Finally, although the broad intervention in some ways is a strength of the study, it could have been too broad to significantly impact individual domains.…”
mentioning
confidence: 99%